Combinative dyebath treatment with activated carbon and UV/H2O2:: a case study on Everzol Black-GSP® - Ince, NH; Hasan, DA; Üstün, B; Tezcanli, G (I W A PUBLISHING, 2002)
Treatability of textile dyebath effluents by two simultaneously operated processes comprising adsorption and advanced oxidation was investigated using a reactive dyestuff, Everzol Black-GSP(R) (EBG). The method was comprised of contacting aqueous solutions of the dye with hydrogen peroxide and granules of activated carbon (GAC) during irradiation of the reactor with ultraviolet light (UV). Control experiments were run separately with each individual process (advanced oxidation with UV/H2O2 and adsorption on GAC) to select the operating parameters on the basis of maximum color removal. The effectiveness of the combined scheme was tested by monitoring the rate of decolorization ana the degree of carbon mineralization in effluent samples. It was found that in a combined medium of advanced oxidation and adsorption, color was principally removed by oxidative degradation, while adsorption contributed to the longer process of dye mineralization. Economic evaluation of the system based on total color removal and 50% mineralization showed that in the case of Everzol Black-GSP(R), which adsorbs relatively poorly on GAC, the proposed combination provides 25% and 35% reduction in hydrogen peroxide and energy consumption relative to the UWH2O2 system. Higher cost reductions are expected in cases with well adsorbing dyes and/or with less costly adsorbents.
Keywords: adsorption; advanced oxidation; degradation; dyebath; granular activated carbon; DYES; Engineering; Environmental Sciences & Ecology; Water Resources